Evaluasi Pelaksanaan Indikator 6t Program Bantuan Pangan Non Tunai di Desa Taman Asri Kecamatan Purbolinggo Kabupaten Lampung Timur - Adelia Putri Anggraini; Ukhti Ciptawaty; Heru Wahyudi; Dedy Yuliawan; Arivina Ratih (Journal on Education, 2024)
Indonesian society is confronted with the significant issue of poverty. The Indonesian government has implemented measures to address the issue of poverty, one of which is the implementation of the Non-Cash Food Assistance (BPNT) programme. The objective of this study is to assess the utilisation of indicators for the 6T Non-Cash Food Assistance Programme (BPNT) in Taman Asri Village. The research methodology employed is descriptive qualitative. The data collection strategies include observation, structured interviews through the distribution of questionnaires, and documentation. The research findings indicate that across all factors, including target, amount, price, time, quality, and administration, the outcomes achieved a score of 79.83% and were classified as effective. Based on the on-target measure, 27.59% of Beneficiary Families (KPM) receiving non-cash food aid (BPNT) can be categorised as affluent families. According to the precise price indication, 21% of respondents said that there was no disparity in the cost of fundamental ingredients at e-warungs compared to other stalls. According to the timely indicator, 22.84% of respondents occasionally received assistance that did not align with the scheduled payout.